Warriors. Tigerstar & Sasha 1, Into the woods - Hunter, Erin (Warriors : Tigerstar & Sasha (Graphic novel), 2008)
When Sasha is forced to leave her home, she must forge a solitary new life in the forest. Life on her own is exciting at first but quickly gets lonely. When Sasha meets Tigerstar, leader of ShadowClan, she wonders whether she would be better off joining the ranks of his forest Clan. But Tigerstar has many secrets, and Sasha must decide whether she can trust him.